EDUKASI DAN PENGETAHUAN TERHADAP PENTINGNYA KARAKTERISTIK BERWIRAUSAHA - Indriyarti, Eko Retno; Murtiningsih, Retno Sari; Tribudhi, Debbie Aryani (Universitas Bunda Mulia, 2023)
Individual entrepreneurial characteristics, especially as seen from generation to generation, have distinct differences. For example, the younger generation has entrepreneurial characteristics such as wanting to succeed quickly, focusing on instant processes, and easily